Geriatric Depression Scale Short Form (GDS-SF) to assess depression in elderly with hypertension - Dwi Novitasari; Sidik Awaludin (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2020)
Depression in the elderly does not receive attention and the symptoms do not always appear. The assessment on 10 elderly showed that five elderly (50%) were normal, three elderly (30%) were suggestive of depression, and two elderly (20%) were indicative of depression. The purpose of this study was to assess depression using the Geriatric Depression Scale Short Form (GDS-SF) in the elderly in Mersi. The design of this study was a descriptive correlation. The population consisted of 105 people who were the members of the Hypertension Care Group. The sample size was 84 people and using Simple Random Sampling. The inclusion criteria was being diagnosed with hypertension for more than one year, while the exclusion criteria was having an activity of daily with total care. The data were analyzed using descriptive statistics. The study subjects were predominately female with 58 people (69.0%). Moreover, 49 respondents (58.3%) were categorized normal with several characteristics: 35 people (89.8%) were satisfied with their life, in good spirits most of the time, though it was wonderful to be alive at the present and full of energy. Then, 39 people (98.0%) lived with a meaningful life, and 37 respondents (93.9%) felt valuable. Depression is categorized into a mental illness that affects the elderly but it is difficult to identify. Hence, it is important to recognize and do research about it to get proper therapy. Nurses can assess the mental aspects of the elderly using the GDS-SF 15.